1994
DOI: 10.1159/000475001
|View full text |Cite
|
Sign up to set email alerts
|

Human Colon Sialidase: Characterization and Activity Levels in Normal Mucosa and Colonic Adenocarcinoma

Abstract: Human colon sialidase has been characterized, and its activity levels in normal mucosa and colonic adenocarcinoma have been determined. Sialidase activity was maximal at pH 5.5. and was unstable with storage at 4 and -20 °C. The bulk of activity was pelletassociated. and could not be released with triton X-100 or 3-([3-cholamidopropyl]- dimethylammonio)-l-propanesulfonate. Using 2’-(4-methylumbelliferyl)α-D-N-acelylneuraminic acid as substrate, the K(m) and V(max) values were estimated to be 0.140 mmol/1 and 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2000
2000
2007
2007

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
2
1
0
Order By: Relevance
“…A low Neu1 level in undifferentiated cells, therefore possibly causing hypersialylation of the carbohydrate portion of glycoproteins, is in line with the observation that malignant cells are often hypersialylated (6,36). We previously observed decreased Neu1 activity in transformed rat 3Y1 fibroblasts (37) and suppression of malignant phenotype of B16 melanoma cells by Neu1 overexpression (22), although one controversial report (38) of increased sialidase activity in human colon tumor probably reflected change in the same Neu1 enzyme, because of the use of 4-methylumbellyferyl-neuraminic acid as substrate. Decreased Neu3 in differentiated cells, on the other hand, would lead to reduction in ganglioside degradation, consistent with previous reports presenting evidence for an increase of GM3 synthase during NaBT treatment (23).…”
Section: Discussionsupporting
confidence: 65%
“…A low Neu1 level in undifferentiated cells, therefore possibly causing hypersialylation of the carbohydrate portion of glycoproteins, is in line with the observation that malignant cells are often hypersialylated (6,36). We previously observed decreased Neu1 activity in transformed rat 3Y1 fibroblasts (37) and suppression of malignant phenotype of B16 melanoma cells by Neu1 overexpression (22), although one controversial report (38) of increased sialidase activity in human colon tumor probably reflected change in the same Neu1 enzyme, because of the use of 4-methylumbellyferyl-neuraminic acid as substrate. Decreased Neu3 in differentiated cells, on the other hand, would lead to reduction in ganglioside degradation, consistent with previous reports presenting evidence for an increase of GM3 synthase during NaBT treatment (23).…”
Section: Discussionsupporting
confidence: 65%
“…Experimental data obtained in our laboratory showed an increased sialidase activity in colorectal carcinoma compared with healthy tissue [24]. This elevated sialidase activity could also be involved in the alterations in the expresion of ·(2,3)-and ·(2,6)-linked sialic acid residues that we observed in tumors from colorectal cancer patients because the ·(2,6)-linkage seems to be much more resistant to mammalian sialidases [25].…”
Section: Discussionsupporting
confidence: 55%
“…There are also several reports on the alterations of endogenous sialidase activity in cancers. Martinez-Zorzano et al (11) have reported that sialidase activity toward synthetic substrate 4-methylumbelliferyl-N-acetylneuraminic acid was increased in human colon cancer as compared to normal mucosa. Moreover, increased sialidase activity was observed in breast cancer (12).…”
Section: Introductionmentioning
confidence: 99%